2015
DOI: 10.1021/ja513209c
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Cu2Si Monolayer with Planar Hexacoordinate Copper and Silicon Bonding

Abstract: Two-dimensional (2D) materials with planar hypercoordinate motifs are extremely rare due to the difficulty in stabilizing the planar hypercoordinate configurations in extended systems. Furthermore, such exotic motifs are often unstable. We predict a novel Cu2Si 2D monolayer featuring planar hexacoordinate copper and planar hexacoordinate silicon. This is a global minimum in 2D space which displays reduced dimensionality and rule-breaking chemical bonding. This system has been studied with density functional th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
280
4
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 366 publications
(321 citation statements)
references
References 57 publications
22
280
4
6
Order By: Relevance
“…Independently,t he Al 2 Cm onolayer and nanoribbons were also predicted by Li, Chen, and co-workers. [166] Quite recently,Y ang and coworkers [167] reported the first global minimum Cu 2 Si monolayer featuring planar hexacoordinate silicon (phSi)a nd planar hexacoordinate copper (phCu). Notably,t he monolayer structures are global minima on the 2D potential surface,w hich make these novel structures promising for experimental realization.…”
Section: Angewandte Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Independently,t he Al 2 Cm onolayer and nanoribbons were also predicted by Li, Chen, and co-workers. [166] Quite recently,Y ang and coworkers [167] reported the first global minimum Cu 2 Si monolayer featuring planar hexacoordinate silicon (phSi)a nd planar hexacoordinate copper (phCu). Notably,t he monolayer structures are global minima on the 2D potential surface,w hich make these novel structures promising for experimental realization.…”
Section: Angewandte Reviewsmentioning
confidence: 99%
“…What are the potential applications of planar hypercoordinate molecules?T od ate,l ittle is known about this possibility.W eh ope that further research will explore whether these unusual materials can have unique catalytic functionality or exotic chemical reactivity,o rc an be used in photoelectronics.Accordingly,recent theoretical studies have identified several promising applications.F or example,a2 D B 2 Cm onolayer including ptC elements is ap romising superconductor with an estimated transition temperature of 19.2 K. [183] aB e 2 Cm onolayer [164] featuring quasi-planar hexacoordinate carbon, and aA l 2 Cm onolayer [165][166] containing ptCs are both semiconducting with amoderate band gap,and thus are promising for potential applications in electronics, optoelectronics and photovoltaics.Furthermore,t he recently predicted highly stable metallic Cu 2 Si monolayer, [167] with exact planar hexacoordinate silicon and planar hexacoordinate copper,might be used as asuperthin electrode in future nanoelectronics.…”
Section: Experimental Realization Of Planar Motifsmentioning
confidence: 99%
“…To gain insight into structural stability of these SbAs monolayers, we have examined their phonon spectra [42]. As shown in Fig.…”
Section: Fig 1 (Color Online) Optimized Structural Configurations Omentioning
confidence: 99%
“…graphene [4][5][6] and graphene-like 2D materials, Cu 2 X (Si, Ge), 7,8 which were named "graphene mimics of the future." As the lightest element in the group of alkaline earth metals, beryllium is a magic element that not only can improve many physical properties when added as an alloying element to metal elements, but also can form both ionic and covalent bonds with many non-metal elements, such as hydrogen, carbon, and nitrogen.…”
Section: Introductionmentioning
confidence: 99%